PERAN KEPEMIMPINAN SEKOLAH DALAM MEWUJUDKAN BUDAYA ORGANISASI YANG EFEKTIF - Windi Widayanti; Ida Mirna; Fuad Abdul Baqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
School leadership plays a strategic role in shaping organizational culture that supports the effectiveness and sustainability of educational institutions. In the context of increasing demands for school quality and accountability, organizational culture has become a crucial factor influencing teachers’ behavior, collaboration, and commitment. This study aims to examine the role of school leadership in fostering an effective organizational culture through a systematic literature-based approach. The study analyzes recent scholarly publications discussing the relationship between school leadership, organizational culture, and organizational behavior in educational settings. The findings indicate that effective school leadership, characterized by participative, value-based, and supportive practices, significantly contributes to the development of a positive organizational culture. Such a culture encourages collaboration, trust, professional commitment, and continuous improvement within schools. This study highlights the importance of leadership capacity development as a key strategy for strengthening organizational culture and improving overall school effectiveness. Keywords: school leadership, organizational culture, organizational behavior, educational leadership, school effectiveness